2013
DOI: 10.1111/phn.12062
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Very Low Birth Weight Based on Perinatal Periods of Risk

Abstract: The findings of this study suggest educating women on the importance of preconception care, prenatal care, and adequate pregnancy weight gain to reduce the odds of having a VLBW infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
6
2
2
Order By: Relevance
“…A previous PPOR analysis conducted in Kansas City identified maternal medical risk as the only significant risk factor of VLBW [7]. A PPOR analysis in Colorado identified maternal age < 20, marital status, and weight gain < 11 pounds as risk factors [10]. However, marital status and weight gain were not evaluated in our analysis; and maternal age < 20 was not associated with an increased risk of VLBW.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A previous PPOR analysis conducted in Kansas City identified maternal medical risk as the only significant risk factor of VLBW [7]. A PPOR analysis in Colorado identified maternal age < 20, marital status, and weight gain < 11 pounds as risk factors [10]. However, marital status and weight gain were not evaluated in our analysis; and maternal age < 20 was not associated with an increased risk of VLBW.…”
Section: Discussionmentioning
confidence: 75%
“…The Kitagawa analyses, which are used to determine the contributors to excess deaths in the maternal health/prematurity category, found that among black infants, 44.5% of the excess deaths were attributed to the distribution of VLBW births, compared to 24.3% among white infants in Kansas City [7]. Other PPOR analyses have identified risk factors for VLBW that include maternal medical risk, maternal anemia, obstetric history, black maternal race, maternal age less than 20 years or greater than 35 years, smoking, inadequate/no prenatal care, parity, maternal weight gain less than 11 pounds, socioeconomic status, and single marital status [2, 10, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Prenatal care is considered an important intervention for infant health. Several studies have highlighted the relevance of prenatal care visits for several birth outcomes such as low birth weight [274][275][276][277][278][279]. 6 However, the mechanism through which prenatal care may affect NTDs is not expected to be the same as other birth outcomes such as birth weight, since NTDs occur within the first 3 weeks of pregnancy.…”
Section: Analytical Models and Study Variablesmentioning
confidence: 99%
“…The IOM recommends a minimum of eleven pounds in weight gain for all pregnant women, including women who were obese prior to pregnancy [413]. Low weight gain during pregnancy has been associated with LBW and VLBW [279,414], whereas high weight gain is associated with macrosomia [414]. Thus, different measures of weight gain were employed for the different birth outcome analyses.…”
Section: Analytical Models and Study Variables Birth Weight Outcomes mentioning
confidence: 99%
See 1 more Smart Citation